Pengabdian Masyarakat: Upaya Penanggulangan Covid-19 Pada Masyarakat di Kelurahan Binong Karawaci Tangerang - Otto Bustani; Yoyok Cahyono; Manorang Sihotang; Intan Rachmina; Suheri Suheri (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
There are some issues that still hard to watch the movement of the society, there are many people where never stick to the protocol rules of health, and so many Cafes and modern and traditional markets disobey to the protocol of health and keep the crowds to gettting close to each other. The aim of this article is to explain the effort of covid 19 Task Force to control the movement of society, to give attention to the protocol of health, and sanctions for disobedient society. The method to use is by giving counseling and informations to the people how important to use self protection from the pandemic covid 19, straight to the spots which we have targetted. Distributes health maskers and self protection tools such as hand sanitizers for free. On the other hand we dont forget to distribute donations such like food to the poor who got impacted by the pandemic covid 19. The result of the community services straightly we can see that many people have awarede and got concerned the danger of the pandemic covid 19 so many people didn’t feel need to go out just for fun when the restrrictions was acknowledged only if it is necessarily. So We can control the movement of people, and more obedient with the protocol, having maskers when went out, washing hands, adn using hand sanitizer. And may people aware to avoid the corwds, taking distance to each other, and those all apply in the Task Force Operation Area in Binong and Tangerang. And that all because of the excellent team work..The implication is the declining of the graphic trend for people that confirmed the infection of the covid 19.